An age-old problem in Little League Baseball - Dixon, Jess C.; Chittle, Laura; Horton, Sean (London : Human Kinetics, Inc., 2015)
The relative age effect (RAE) has become a well-studied consequence of organizations utilizing a cutoff date to establish age cohorts. Within this case study, students will explore and learn how to perform various statistical analyses (i.e., chi-square, effect sizes, standardized residuals) to determine whether the RAE exists among those who competed in the 2011 and 2012 Little League World Series (LLWS). Students will learn about the mission and history of Little League Baseball (LLB) and discuss potential changes and/or strategies that could be used by the organization to make the LLWS more inclusive. Furthermore, students can use the knowledge gained from this case study to critically analyze the current status of various other sport organizations to help develop potential strategies to ensure fairness and equality for all participating athletes.
Originally published in Dixon, J., Chittle, L., & Horton, S. (2015). An age-old problem in Little League Baseball. Case Studies in Sport Management, 4(1), 1-6. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Little League Baseball (Organization) -- Case studies; Baseball -- Social aspects -- Case studies; Fairness -- Case studies; Sports -- Moral and ethical aspects -- Case studies